2016
DOI: 10.1159/000458144
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Development of Fistulae and Stenoses in Crohn Disease Patients in the Swiss Inflammatory Bowel Disease Cohort

Abstract: Background: Fistulae and stenoses represent frequent and severe complications in patients with Crohn disease (CD). Our study aimed to identify risk factors for fistula and stenosis formation in CD patients. Summary: We retrieved data of 1,600 CD patients from the nationwide Swiss Inflammatory Bowel Disease Cohort Study (SIBDCS). The risk for fistulae and stenoses in relation to gender, age at diagnosis, smoking status at diagnosis, and ileal involvement at diagnosis were analyzed. In the multivariate analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Previous studies already described a role for a number of SNPs located within the TNFSF15 gene locus as being associated with disease progression in CD patients. 13 , 32 In our paper we identified a further SNP within this gene locus, namely SNP rs4246905, to protect from disease progression, confirming the role of TNFSF15 in this regard. On a functional level, TNFSF15, also known as TL1A, and its receptor DR3 have been shown to be widely expressed in inflamed intestinal tissue of IBD patients.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Previous studies already described a role for a number of SNPs located within the TNFSF15 gene locus as being associated with disease progression in CD patients. 13 , 32 In our paper we identified a further SNP within this gene locus, namely SNP rs4246905, to protect from disease progression, confirming the role of TNFSF15 in this regard. On a functional level, TNFSF15, also known as TL1A, and its receptor DR3 have been shown to be widely expressed in inflamed intestinal tissue of IBD patients.…”
Section: Discussionsupporting
confidence: 69%
“…Clinical parameters, such as the initial CD location at diagnosis, smoking and the age of the patient at diagnosis, have been established as risk factors for a progression to B stage. 3,4,[10][11][12][13][14] Genetic risk factors for the development of penetrating CD include African American origin and family history. 15 In addition, it has been demonstrated that host genetics and particularly the presence of specific single nucleotide polymorphisms (SNPs) within IBD risk genes critically impact the pathogenesis of CD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With CD, there is a risk of complications such as stenosis or fistulas in the intestine. Perianal disease may be developed with fistulas and/or abscesses (51). Primary sclerosing cholangitis in CD and UC is a chronic cholestatic disease affecting predominantly males with a median age of ~40 years.…”
Section: Disease Severity and Complicationsmentioning
confidence: 99%
“…In general, the behavior of CD can be categorized into three phenotypes including inflammatory (non-stricturing, non-penetrating), stricturing and penetrating (fistulizing) disease[ 4 ]. Strictures consist of inflammatory, fibrotic or mixed processes leading to acute abdominal pain or obstruction and are a risk factor for developing internal fistulae and cancer[ 5 , 6 ]. At diagnosis, only a tenth of CD patients will present with a stricture however, up to one third of patients will ultimately develop stricturing within ten years of diagnosis, predominantly in the ileum[ 7 ].…”
Section: Introductionmentioning
confidence: 99%